2012
DOI: 10.1111/j.1460-9568.2011.07979.x
|View full text |Cite
|
Sign up to set email alerts
|

Levodopa influences striatal activity but does not affect cortical hyper‐activity in Parkinson’s disease

Abstract: Motor studies of Parkinson's disease (PD) have shown cortical hypo-activity in relation to nigrostriatal dopamine depletion. Cognitive studies also identified increased cortical activity in PD. We have previously suggested that the hypo-activity/hyper-activity patterns observed in PD are related to the striatal contribution. Tasks that recruit the striatum in control participants are associated with cortical hypo-activity in patients with PD, whereas tasks that do not result in cortical hyper-activity. The put… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 41 publications
9
36
2
Order By: Relevance
“…In accordance with these results, we have recently indicated that even within a motor task that solicits both motor and cognitive CBG regions, levodopa has an effect on the motor CBG circuit, but not the cognitive one (Martinu et al, 2012). Although the effect of levodopa on motor symptoms is beneficial, improvement can be seen in some tasks whereas performance on others worsens (Gotham, Brown, & Marsden, 1988;Cooper et al, 1992).…”
Section: Levodopa Treatmentsupporting
confidence: 56%
“…In accordance with these results, we have recently indicated that even within a motor task that solicits both motor and cognitive CBG regions, levodopa has an effect on the motor CBG circuit, but not the cognitive one (Martinu et al, 2012). Although the effect of levodopa on motor symptoms is beneficial, improvement can be seen in some tasks whereas performance on others worsens (Gotham, Brown, & Marsden, 1988;Cooper et al, 1992).…”
Section: Levodopa Treatmentsupporting
confidence: 56%
“…All patients came for two counterbalanced scanning sessions (one OFF medication, one ON levodopa), and were asked to withdraw from all anti-parkinsonian medications for a minimum of 12 hours prior to each appointment (see [11]). Participants remained off medications for the OFF session.…”
Section: Methodsmentioning
confidence: 99%
“…Participants performed SI, ET and control (CTL) finger movements using left and right hands separately during functional MRI acquisitions in a pseudo-randomised order across runs, in both ON and OFF conditions (previously described in [11]). Each block began with written instructions, displayed for 2.5s, followed by the appearance of five squares oriented in a horizontal row on the screen, each corresponding to a button on the response box.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations